Associations of Polypharmacy and Inappropriate Medications with Adverse Outcomes in Older Adults with Cancer: A Systematic Review and Meta‐Analysis. (30th September 2019) - Mohamed, Mostafa R.; Ramsdale, Erika; Loh, Kah Poh; Arastu, Asad; Xu, Huiwen; Obrecht, Spencer; Castillo, Daniel; Sharma, Manvi; Holmes, Holly M.; Nightingale, Ginah; Juba, Katherine M.; Mohile, Supriya G.
Abstract: Background: Polypharmacy (PP) and potentially inappropriate medications (PIM) are highly prevalent in older adults with cancer. This study systematically reviews the associations of PP and/or PIM with outcomes and, through a meta‐analysis, obtains estimates of postoperative outcomes associated with PP in this population. Materials and Methods: We searched PubMed, Embase, Web of Science, and Cochrane Register of Clinical Trials using standardized terms for concepts of PP, PIM, and cancer. Eligible studies included cohort studies, cross‐sectional studies, meta‐analyses, and clinical trials which examined outcomes associated with PP and/or PIM and included older adults with cancer. A random effects model included studies in which definitions of PP were consistent to examine the association of PP with postoperative complications. Results: Forty‐seven articles met the inclusion criteria. PP was defined as five or more medications in 57% of the studies. Commonly examined outcomes included chemotherapy toxicities, postoperative complications, functional decline, hospitalization, and overall survival. PP was associated with chemotherapy toxicities (4/9 studies), falls (3/3 studies), functional decline (3/3 studies), and overall survival (2/11 studies). A meta‐analysis of four studies indicated an association between PP (≥5 medications) and postoperative complications (overall odds ratio, 1.3; 95% confidence interval [1.3–2.8]). PIM was associated with adverse outcomes in 3 of 11 studies. Conclusion: PP is associated with postoperative complications, chemotherapy toxicities, and physical and functional decline. Only three studies showed an association between PIM and outcomes. However, because of inconsistent definitions, heterogeneous populations, and variable study designs, these associations should be further investigated in prospective studies. Abstract : This review evaluates the association of polypharmacy and potentially inappropriate medications with outcomes in older adults with cancer.